RBM15 suppresses hepatic insulin sensitivity of offspring of gestational diabetes mellitus mice via m6A-mediated regulation of CLDN4 - Fang, Jie; Wu, Xiafei; He, Jie; Zhang, Hanwen; Chen, Xuyang; Zhang, Hua; Novakovic, Boris; Qi, Hongbo; Yu, Xinyang (Molecular medicine (Cambridge, Mass.), 2023)
Gestational diabetes Mellitus (GDM) is a common pregnancy-specific disease with high morbidity, which is linked to a high risk of obesity and diabetes in offspring. N6-methyladenosine modification of RNA is emerging as an important epigenetic mechanism that is widely manifested in many diseases. This study aimed to investigate the mechanism of m6A methylation in metabolic syndrome in offspring result from intrauterine hyperglycemia. GDM mice were established by feeding a high-fat diet 1 weeks before pregnancy. The m6A RNA methylation quantification kit was used to detect liver tissue methylation levels. PCR array was used to determine the expression of the m6A methylation modification enzyme. Immunohistochemistry, qRT-PCR, and western blot were used to examine the expression of RBM15, METTL13, IGF2BP1, and IGF2BP2. Subsequently, methylated RNA immunoprecipitation sequencing combined with mRNA sequencing, followed by dot blot and glucose uptake tests, were performed. In this study, we found that offspring from a GDM mother were more vulnerable to glucose intolerance and insulin resistance. GC-MS revealed significant metabolic changes including saturated fatty acids and unsaturated fatty acids in liver of GDM offspring. We also demonstrated that global mRNA m6A methylation level was significantly increased in the fetal liver of GDM mice, indicating epigenetic change may have a strong relationship with the mechanism of metabolism syndrome. Concordantly, RBM15, the RNA binding methyltransferase, was upregulated in the liver. In vitro, RBM15 suppressed insulin sensitivity and increased insulin resistance through m6A-regulated epigenetic inhabitation of CLDN4. Moreover, MeRIP-sequencing and mRNA-sequencing revealed that differently regulated genes with differential m6A peaks were enriched in metabolic pathways. Our study revealed the essential role of RBM15 in insulin resistance and the effect of RBM15-regulated m6A modification in the metabolic syndrome of offspring of GDM mice.